Journey towards sustainable business unveiling innovation and entrepreneurial growth- in Indian framework - Somrita Chakraborty (INTERNATIONAL CONFERENCE OF ECONOMICS AND BUSINESS, 2025)
Sustainability refers to the situation where the present condition is made to be fulfilled without compromising the existing or future conditions. An entrepreneur, who eyes on the success of his own business considering social and environmental benefits of the society, can be considered as a sustainable entrepreneur. Developing the product, innovating creative ways, taking competitive advantage of the product combining economic, social and environmental factors into the goal, action as well as planning of the organization requires different alterations into the ongoing business practices. Sustainability implicitly looks upon harmony, cooperation among businesses pursuing the overall welfare of the society. Inspite of extreme obstacles, taking sustainability in consideration and initiating innovative processes is considered as a unique viewpoint linking socio-economic values emphasizing on the welfare of the future generation. This paper deals with the factors that might help to sustain the entrepreneurial growth that eventually leads to a sustainable business growth.